Implementation of Differentiated Learning in Class IV Fiqh Subjects Material on Procedures for Prayer in Sickness at MI Muhammadiyah Semondo Gombong Kebumen - Wakhidati, Nurul; Siti Fatimah (International Journal of Basic Educational Research, 2024)
The research objectives are: (1) to find out how differentiated learning is implemented in the Merdeka Curriculum in terms of content, process, product and learning environment in class IV fiqh subjects at MI Muhammadiyah Semondo; (2) to determine the supporting and inhibiting factors faced in implementing differentiated learning. This research is in the form of Qualitative Research. The students studied were class IV MI Muhammadiyah Semondo with a total of 50 children. The method used in this research is a qualitative method using field research. The data collected was implementation data, supporting and inhibiting factors for differentiated learning in class IV fiqh subjects at MI Muhammadiyah Semondo. Data collection techniques in this research used observation, interviews and documentation. The data analysis used is inductive/qualitative data analysis. The data analysis techniques used are data collection, data condensation, data presentation, and drawing conclusions. Based on the research results, it can be concluded that: (1) implementing differentiated learning in class IV fiqh subjects at MI Muhammadiyah Semondo, the teacher begins by carrying out an initial assessment to determine the students' learning styles. Next, the teacher prepares learning steps that contain differentiation of content, processes, products and learning environments, which are in accordance with the needs and interests of students; (2) supporting factors for differentiated learning, namely the existence of a policy of implementing an independent curriculum, support from the madrasa head, and a supportive learning environment. While the inhibiting factors are managing time to be effective and difficulties in the assessment process, the solution is to make clear learning plans and detailed assessment rubrics.